(untitled) (Itinera, 2022)
The aim of this essay is to outline the genesis of a plural conception of temporality within Gilles Deleuze’s thought, using as a starting point his reflection on the Kantian sublime and showing how this reflection has significant repercussions in place of the pages that Deleuze dedicates to painting. To show the implications of the overcoming that Deleuzian conception tries to make on the ordinal character of Kantian temporality, we will first focus on the role played by imagination within the doctrine of faculties; then, we will focus on the passage from the ordinal temporality disclosed by Kant to the plural one conceived by Deleuze. Finally, we will show how this new temporality manifests itself through Deleuzian aesthetic conceptions in the field of painting, with reference to the notions of "actual" and "virtual" and to the role that the Kantian sublime continues to play in this phase of Deleuzian thought.